Environmental Conditions Affecting the Expression of the SuoM Gene: An Stress Sigma Factor in M. smegmatis - Nailet Arráiz; L Salazar; H Takiff (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2002)
Sigma factors associate with the RNA polymerases and confer specificity in the recognition of promoter regions. This provides a transcriptional regulatory level, that determines that a sets of genes is expressed according to the physiological necessities of bacterial cell. The sequence analysis of the region of replication origin of Mycobacterium smegmatis revealed the presence of a reading frame with capacity to codify a sigma factor of the ECF subfamily ("extracytoplasmic function"), which are characterized by directing the transcription of genes in response to changes in the environmental conditions. Transcriptional fusions PsuoM-lacZ' in operon fusion plasmid pJEM15 were constructed with the objective of identifying the environmental conditions that stimulate the expression of the isolated gene, named suoM ("sigma linked to the origin in mycobacteria"), The constructions were introduced by electro-poration in M. smegmatis and the cells were grown under different environmental stress conditions. The promoter activity of the gene suoM was measured by B-galactosidasa expression. An increase of 2.0-3.5 times in the promoter activity was observed when the cells were transferred to 45°C and when the culture reached stationary growth phase. The results suggest that suoM could be involved in the regulation of gene expression in conditions of high temperature and in the stationary growth phase, inductive conditions that could have some significance in the pathogenic potential of mycobacteria and the ability of M. tuberculosis to cause latent infection.